Cognitive Stylistic Component of Socio-Cultural Activity Manager Training - Kostiuchenko Оlena; Dykhnych, Liudmyla; Cristóvão, Artur (Socio-Cultural Management Journal, 2021)
Introduction. The relevance of the study is due to the need to train managers with a systemic adaptive ability to operate with technologies, knowledge, and information, the ability to change and adapt to new needs of socio-cultural reality in terms of integration into the global information space. Purpose and methods. The purpose of the article is to determine the cognitive and stylistic features of the manager’s personality, substantiate their role in his professional formation and development in the learning environment. The methodological basis is the principles of scientific knowledge (determinism, system, development), the provisions of activity, system, and personality-oriented approaches. Results. The researchers systematized scientific approaches to the cognitive styles’ definition, substantiated their role in professional development and manager’s personality development. Cognitive styles are defined as cognition strategies, cognitive-stylistic dimension of personality, which determines the ways of setting and solving problems, decision-making and goal-setting. The psychological parameters and characteristics of cognitive-stylistic features are singled out, the factors of cognitive-stylistic development of the manager’s personality in the training conditions are determined. Conclusions. The scientific novelty consists in concepts’ definition of professional formation cognitive-stylistic component and the manager’s personality development and in highlighting the optimal parameters and characteristics of cognitive styles for its successful functioning. The practical significance of the study is to reveal the possibilities of applying knowledge about cognitive and stylistic features in the learning optimization, cognitive activity development of the socio-cultural sphere managers.